Wine tourism in Europe and Ukraine - Shyliaiev, Dmytro; Yurchuk, Lyudmila (My University, 2015)
Today wine tourism has become an essential part of our life because of growing vine consumption as a culture. Many progressive European countries implement this kind of tourism long ago, and Ukraine must to go their way.
Keywords: wine tourism; винний туризм; кафедра іноземних мов професійного спрямування